Correlation of interleukin-17 with disease activity and hand joint damage in patients with rheumatoid arthritis - Jeffrey Arthur Ongkowijaya; Bambang Setiyohadi; Ida Ayu Ratih Wulansari Manuaba; Yoga I Kasjmir (Indonesian Rheumatology Association, 2010)
Background: Rheumatoid arthritis (RA) is a disease involving various types of cytokines. One of them is interleukin-17 (IL-17), which is known to have a pleiotropic effect on various of cells and is thought to be a cytokine effector contributing to the pathogeniccondition in RA.Methods: The study was conducted on 46 RA patients at rheumatology clinic at the Cipto Mangunkusumo General Hospital who were diagnosed based on the 1987 American College of Rheumatology criteria. Sample selection was done using consecutive sampling. Tests on patients were conducted to collect data needed to obtain the scores for 28-joint Disease Activity Score (DAS28), global health visual analogue scale, swollen joint count, tender joint count, sedimentation rate, Sharp score (radiograph of both hands), and the IL-17 level.The correlation between IL-17 level and DAS28 wasÂ calculated using the Pearsonâ€™s correlation test while the correlation between IL-17 level and Sharp score was calculated using the Spearmanâ€™s test.Results: The majority of patients (87%) were women. The largest percentage was in the 51- to 60-year-old group (39.1%). Most patients (43.1%) had moderate disease activity. There were 27 patients (58.69%) with positive rheumatoid factor. The mean IL-17 level was17.28 pg/mL with a standard deviation of 11.43 pg/mL. There was no correlation of IL-17 level with disease activity (p = 0.446, r = 0.021) and Sharp score (p = 0.304, r = 0.077) in subjects of this study.Conclusion: There was no signifi cant correlation of IL-17 with disease activity and joint damage.